STUDY OF THE ACTN3 GENE POLYMORPHISM TO ASSESS THE PHYSICAL PERFORMANCE OF ATHLETES - Yakubov Mirakbar Daniyarovich; Dalimova Dilbar Akbarovna (International Engineering Journal For Research & Development, 2022)
In the study of the distribution of genotypes of the ACTN3 gene associated with both speed-strength capabilities and endurance, 397 people took part, of which 296 were athletes of various specializations and 101 control groups to determine the frequency of occurrence of genotypes of the R557X polymorphism of the ACTN3 gene in Uzbek athletes. People involved in cycling, boxing, rugby, football, rowing and control groups - people who are not involved in sports. Thus, the results of the distribution of genotypes with R577X polymorphism of the ACTN3 gene in rowing athletes indicate a favorable effect of the presence of the R allele (genotypes RR and RX) on cycling and rowing